Software para fertirrigação da cultura do morangueiro - Garcia, Roberta Bonamichi Guidi (2012)
The practice of fertirrigation is quite common in Brazilian agriculture and is widely used in strawberry plantings, substantially improving the quality of fruit production. The objective of this work is to design and implement a computer system for the irrigation of strawberry culture with automatic calculation and detailed control of the amount of nutrients through irrigation water at various stages of development of the strawberry crop. The first stage of work was developed at the University José do Rosário Vellano - UNIFENAS Alfenas Campus, and the step of creating the software was held in IFSULDEMINAS, Inconfidentes Campus. For the modeling and creation of the database was used and free software tool IBExpert Firebird, the programming language used was Delphi 7, which runs on the Windows platform and for the handling of the database language, SQL was used. The application has features of producer records, property, operator, cultivating, planting area, fertilizer, and database, and calculates the amount of nutrients based on the recommendations for the use of fertilizers in Minas Gerais, 5 ª approach to fertilization mineral NPK, water to be used for planting, and how long this application should be, enables consultations to the database and generates reports with information about the daily management of fertirrigation, being easy to use for technicians, agronomists and farmers.